2018
DOI: 10.1186/s12913-018-2873-8
|View full text |Cite
|
Sign up to set email alerts
|

Evidence to service gap: cardiac rehabilitation and secondary prevention in rural and remote Western Australia

Abstract: BackgroundCardiovascular disease (CVD), a leading cause of morbidity and mortality, has similar incidence in metropolitan and rural areas but poorer cardiovascular outcomes for residents living in rural and remote Australia. Cardiac Rehabilitation (CR) is an evidence-based intervention that helps reduce subsequent cardiovascular events and rehospitalisation. Unfortunately CR attendance rates are as low as 10–30% with rural/remote populations under-represented. This in-depth assessment investigated the provisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 25 publications
0
20
0
1
Order By: Relevance
“…One study found that more than 70% of Aboriginal patients with AF and CHA 2 DS 2 ‐VASc scores of 2 or more were not receiving oral anticoagulants . Warfarin was the main oral anticoagulant available during our study period, but adequate monitoring of patients’ international normalised ratio (INR) in rural and remote communities is difficult because of remoteness, limitations in service availability and culturally appropriate referral pathways, and family caring responsibilities. Recent Australian guidelines recommend novel oral anticoagulants (NOACs) for Aboriginal people with non‐valvular AF because they overcome many of the logistic and clinical barriers associated with warfarin .…”
Section: Discussionmentioning
confidence: 97%
“…One study found that more than 70% of Aboriginal patients with AF and CHA 2 DS 2 ‐VASc scores of 2 or more were not receiving oral anticoagulants . Warfarin was the main oral anticoagulant available during our study period, but adequate monitoring of patients’ international normalised ratio (INR) in rural and remote communities is difficult because of remoteness, limitations in service availability and culturally appropriate referral pathways, and family caring responsibilities. Recent Australian guidelines recommend novel oral anticoagulants (NOACs) for Aboriginal people with non‐valvular AF because they overcome many of the logistic and clinical barriers associated with warfarin .…”
Section: Discussionmentioning
confidence: 97%
“…Such studies on mental health in the elderly population in rural and remote regions are of utmost importance, considering the special characteristics of these areas, such as low population density with small settlements and poor accessibility to healthcare services. 3 Research suggests that several factors have an impact on mental health in the elderly. Marriage and a close social network have been positively associated with psychological well-being and happiness, [4][5][6][7] whereas low socio-economic status, stressful life events, and living alone 8 have been identified as risk factors for the development of psychopathological symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…3 Research suggests that several factors have an impact on mental health in the elderly. Marriage and a close social network have been positively associated with psychological well-being and happiness, [4][5][6][7] whereas low socio-economic status, stressful life events, and living alone 8 have been identified as risk factors for the development of psychopathological symptoms. 9,10 Moreover, smoking and alcohol consumption have been reported to correspond with increased levels of depression in elderly people.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] Despite the recent policy focus on maintain and enhance continuity of care (COC) within hospital care, [3] rehabilitation research reports that there is limited communication, transfers delays and administrative barriers between rehabilitation team and other services. [1,4,5] Inpatients receiving physiotherapy report a lack of transfer of information and consistency of care between professionals. These concerns are related to content, synchronization, or sequence of the physiotherapy activities.…”
Section: Introductionmentioning
confidence: 99%
“…These measures have examined features of the chronology of sequential care or transfers delays. [2,4,5,7,8,13,14] Likely, continuity from patient's perspective is not often evaluated because of the lack of an agreed definition and suitable measurement tools.…”
Section: Introductionmentioning
confidence: 99%